Foreign Direct Investment Modes and Local Backward Linkages - Chrysovalantou Milliou; Apostolis Pavlou (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study a multinational enterprise's (MNE) choice of foreign direct investment (FDI) mode in a vertically related market with local input sourcing. We show that the vertical structure of the market and its features play a crucial role for the MNE.s decision: backward linkages, enhanced upstream bargaining power, use of non-linear contracts, and interim unobservability of contract terms favor cross-border acquisition relative to greenfield investment. We also show that while a cross-border acquisition reduces welfare, greenfield investment can be welfare-improving. These results suggest that policy should distinguish among FDI modes as well as among markets with more or less dependence on backward linkages.
Keywords: L13; F12; F23; 330; foreign direct investment; greenfield investment; acquisition; vertical relations; two-part tariffs